Obesity in adolescence linked to physical inactivity which improves the practice of physical exercises in bodybuilding rooms (Research, Society and Development, 2023)
Introduction: Obesity in adolescence is a worrying factor, therefore, it is necessary to guide this public about obesity at this stage in which structured physical exercise for these young people, linked to good eating habits, is important for maintaining health. It acts in reducing overweight and obesity, raising self-esteem, and improving their quality of life. Objective: It is to understand the possibilities and how physical exercise practiced in bodybuilding gyms can help in the treatment of early adolescent obesity. Justification: The work is justified in the orientation of the teenager about the sedentary lifestyle as one of the main causes of the increase of the corporal weight, in order to propose the weight training as a preventive means. Methodology: The present study is a narrative review, because according to the authors De Oliveira et al. (2022) narrative reviews are classified as a literature review that provide narrative and comprehensive syntheses of information once it has already been published. Final considerations: Therefore, it is inferred that the present work shows that routine bad habits are the main factors that contribute to this comorbidity that has been plaguing these young people at an early age, along with the rise of technology.